Moderating Role of Financial Resilience: Relationship Between Financial Behavior and Well-being - Rahmah, Wahyuni; Pratama, Muhammad Faried; Baheri, Jusbair (Journal of Business Management and Economic Development, 2026)
The increasing complexity of financial demands faced by working millennials calls for a more comprehensive understanding of the factors influencing financial well-being, particularly in Kendari City. This study aims to analyze the effects of interpersonal influence, financial self-efficacy, and financial awareness on financial well-being, with financial behavior serving as a mediating variable and financial resilience as a moderating variable. Data were collected through structured questionnaires administered to 289 working millennials who earn their own income. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that interpersonal influence, financial self-efficacy, and financial awareness have a significant effect on financial behavior. Furthermore, financial behavior and financial resilience significantly influence financial well-being. Financial behavior has been shown to mediate the relationships among interpersonal influence, financial self-efficacy, financial awareness, and financial well-being. In addition, financial resilience strengthens the relationship between financial behavior and financial well-being, acting as a protective resource in facing economic pressures.